Quantification Process, Sociometric, Numerical Scale 9 and Social Interpretation Research in Social Humanity under Artifical Intelligent Era - Suriadi, Jadi Suriadi (University of Darussalam Gontor Press, 2024)
This research delves into the intricate measurement of the Harmony Index in Bekasi City within the context of the Artificial Intelligent era, employing a quantification process, sociometric analysis, and a numerical scale of 9. The study explores the social dimensions that impact harmony and utilizes AI to extract insights from non-structural data, offering a comprehensive understanding of the community's goodness, beneficial and well-being. The variables Xi are assessed in terms of Perception, Participation, and Acceptability (PPA) perspectives, and their weighted scores contribute to the Harmony Index formula. Statistical analyses, including correlation, variance, and standard deviation, enable the evaluation of the data, leading to profound social interpretations. The study identifies regularities, response rates, and significance scores while categorizing respondents. This research enhances our understanding of harmony, informs policy recommendations, and paves the way for community betterment. One significant outcome of the study is the categorization of respondents based on their levels of engagement, classifying them as engaged, moderate, or non-engaged. This categorization provides a nuanced understanding of how different segments of the community interact with the variables under investigation. Furthermore, the research successfully distilled essential insights from a vast pool of non-structural narrative data, narrowing down the analysis to the most relevant and informative content, ultimately enhancing the depth and quality of the findings.